Manifestation of socially destructive viewpoints of protestant churches in the context of Russia’s war crimes against Ukraine - Луцан, Ігор; Марчук Marchuk, Олександр Танасійович Oleksandr (My University, 2023)
The main focus of this research article is on manifestations of socially destructive viewpoints in the conditions of the Russia-Ukraine war, which may have potentially devastating consequences that could undermine social bonds, particularly in the context often take on a destructive character and can be aimed at destabilizing social connections, including inertia in finding effective mechanisms of protection and mutual support. The material has been processed within the framework of the project “Social Functionality of Religion in Conditions of Extreme Peril: Ideological-Theoretical and Practical Dimensions” under the state registration number: 0121U109446.
Keywords: Protestantism, the social activity of the Church, destructive manifestations, pacifism, war